Figurative language in science popularisation:similes as an explanatory strategy in TED talks - Scotto di Carlo, Giuseppina (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
This paper investigates the use of figurative language as one of the main features of TED (Technology, Entertainment, and Design) Talks,a new science popularising genre. Drawing upon Wikberg’s (2008) similes classification,which analyses the patternsas ADJ/ADV as, is like N, is like V-ing N, and V like N,the paper examines the use of similes as an explanatory strategy for knowledge dissemination. Focussing on a qualitative and quantitative analysis of the TED talks held between 2006 and 2012,the study shows how TEDsters use similes to compare complex scientific concepts to everyday life experiences;to breach the expert/non expert barrier so that non-experts can participate in the scientific findings;and to look at science as ideas to be discussed rather than information to be passively received. The study also reveals that rather than focussing on culture-bound similes, these audience-oriented talks tend to avoid local cultural references that would not be understood abroad.